(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
In this article, the importance of psychological relationships between teachers and students in the educational process is analyzed. The role of a positive psychological environment, pedagogical communication, emotional support, and mutual trust in improving educational effectiveness is examined from a scientific perspective. In addition, the impact of negative relationships on students’ motivation, activity, and psychological state is also considered.